2023
DOI: 10.1002/eat.23976
|View full text |Cite
|
Sign up to set email alerts
|

Project Body Neutrality: Piloting a digital single‐session intervention for adolescent body image and depression

Abstract: Data Availability Statement:The data and code that support the findings of this evaluation, excluding identifying information, are openly available at https://osf.io/w82bf/.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…SSIs have also been shown to be effective with non-clinical populations at reducing body image concerns and eating psychopathology [16][17][18][19]. SSIs use a variety of strategies including psychoeducation [16,18,19], imagery rescripting [17,18], and cognitive dissonance interventions [16,17].…”
Section: Prior Workmentioning
confidence: 99%
See 1 more Smart Citation
“…SSIs have also been shown to be effective with non-clinical populations at reducing body image concerns and eating psychopathology [16][17][18][19]. SSIs use a variety of strategies including psychoeducation [16,18,19], imagery rescripting [17,18], and cognitive dissonance interventions [16,17].…”
Section: Prior Workmentioning
confidence: 99%
“…SSIs have also been shown to be effective with non-clinical populations at reducing body image concerns and eating psychopathology [16][17][18][19]. SSIs use a variety of strategies including psychoeducation [16,18,19], imagery rescripting [17,18], and cognitive dissonance interventions [16,17]. In all studies involving a control group, participants who engaged with the SSIs showed a comparative improvement in eating pathology [16][17][18].…”
Section: Prior Workmentioning
confidence: 99%
“… 52 However, some have expressed concern about potential pitfalls of body positivity, including its reinforcement of a focus on appearance. 53 , 54 The following section briefly reviews existing research investigating the impact of body-positive content on social media.…”
Section: Body Positivity On Social Mediamentioning
confidence: 99%
“…Other recently-evaluated SSIs incorporating B.E.S.T. components have shown promise in reducing parental accommodation of child anxiety (Sung et al, 2021), body dissatisfaction in adolescents (per an open trial by Smith et al, 2023), and internalized stigma in LGBTQ+ adolescents (Shen et al, 2023).…”
Section: Digital Ssis For Youth Mental Health 15mentioning
confidence: 99%